The Effect of Distributive Justice, Procedural Fairness and Financial Compensation on Employee Loyalty in a Manufacturing Company in Bali - Irvan, Muhammad; Munif, Rifqy; Herdiansyah, Muhammad Reza (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This study aimed to analyze the influence of distributive justice, procedural justice, and financial compensation on employee loyalty in a manufacturing company in Bali. The problem addressed was the impact of perceived fairness and compensation on employee loyalty. A quantitative approach was used, with data collected through questionnaires distributed to 50 employees. The data were analyzed using multiple linear regression. The findings revealed that distributive justice and financial compensation significantly and positively influenced employee loyalty. However, procedural justice did not have a significant individual impact but contributed positively when combined with the other two variables. The results indicated that fair distribution of earnings and adequate financial compensation enhance employee loyalty, while the role of procedural justice is more significant when considered alongside other fairness aspects. These findings suggest that management should prioritize improving distributive justice and financial compensation strategies to foster higher employee loyalty. This study contributes to the literature on human resource management by highlighting the importance of fairness in compensation and decision-making processes. Further research is recommended to explore other variables affecting employee loyalty and to test these findings across different industries.